Exploring the Integration of STEAM Education through Multi and Interdisciplinary Approaches in Elementary Schools: The Role of Professional Learning Communities at SDIT Darut Tauhid Gabus - Hanik Ristiana; Joko Widodo; Agus Wahyudin; Tri Suminar (International Conference on Science, Education, and Technology, 2023)
The integration of Science, Technology, Engineering, Arts, and Mathematics (STEAM) education in elementary school curriculum has gained prominence as a means to enhance the quality of education. This study aims to investigate the effectiveness of Professional Learning Communities (PLCs) in integrating STEAM education through multi and interdisciplinary approaches at SDIT Darut Tauhid Gabus. A qualitative research approach with a case study design was employed to gather comprehensive insights. Data collection involved observation, interviews, and document analysis. The findings of this study suggest that PLCs serve as a promising approach for integrating STEAM education in the elementary school curriculum. Through PLCs, teachers are encouraged to collaborate, reflect upon their practices, and continuously improve their teaching methods. The interdisciplinary and hands-on nature of STEAM education fosters critical thinking, problem-solving, and creativity skills among students. Therefore, the implementation of PLCs in elementary schools, such as SDIT Darut Tauhid Gabus, holds potential for improving the quality of education and preparing students to thrive in the challenges of the 21st century